Outcomes of Remote Pathology Instruction in Student Performance and Course Evaluation. (13th December 2021) - Hernandez, Tahyna; Fallar, Robert; Polydorides, Alexandros D.
The coronavirus disease 2019 (COVID-19) pandemic has disrupted undergraduate medical education, including preclinical class-based courses, by requiring social distancing and essentially eliminating in-person teaching. The aim of this study was to compare student performance and satisfaction before and after implementation of remote instruction in a first-year introductory pathology course. Assessments (3 quizzes, 1 practical exam, and 1 final) were compared between courses given before (January 2020) and during (January 2021) the COVID-19 pandemic, in terms of mean scores, degree of difficulty, and item discrimination, both overall and across different question types. Students' evaluations of the course (Likert scale-based) were also compared between the 2 years. Significantly higher mean scores were observed during remote instruction (compared to the prior, in-person year) on verbatim-repeated questions (94.9 ± 8.8 vs 89.4 ± 12.2; P = .002) and on questions incorporating a gross specimen image (88.4 ± 7.5 vs 84.4 ± 10.3; P = .007). The percentage of questions that were determined to be moderate/hard in degree of difficulty and good/very good in item discrimination remained similar between the 2 time periods. In the practical examination, students performed significantly better during remote instruction on questions without specimen images (96.5 ± 7.0 vs 91.2 ± 15.2; P = .004). Finally, course evaluation metrics improved, with students giving a higher mean rating value in each measured end point of course quality during the year of remote instruction. In conclusion, student performance and course satisfaction generally improved with remote instruction, suggesting that the changes implemented, and their consequences, should perhaps inform future curriculum improvements.